Promoting and sustaining a quality teacher workforce - LeTendre, Gerald K.; Wiseman, Alexander W., 1968- (Bingley, U.K. : Emerald, 2015)
Teacher effectiveness and teacher quality have become the focus of intense international attention and concern. Around the world, governments are modifying existing certification requirements or implementing value-added modeling in order to qualify teachers without planning for the long-term consequences of these actions. The book brings together scholars from multi-disciplinary and international backgrounds to address two critical areas: (1) what existing cross-national measures of teacher effectiveness and teacher quality are most promising, and how can these be aligned to maximize their research potential; and (2) what core constructs of teacher quality or effectiveness are missing, and how can cross-national research help identify these. Identifying both what is used and what is missing in the international and comparative analysis and reform of teacher quality is key to informing evidence-based educational policy formation around teacher quality.
Introduction : the challenges of teacher effectiveness and quality worldwide / Gerald K. LeTendre, Alexander W. Wiseman -- The UNESCO Institute for Statistics (UIS) strategy on teacher statistics : developing effective measures of quantity and quality in education / Peter Wallet -- Measuring teachers' professional learning activities in international context / Motoko Akiba -- Regimes of teacher beliefs from a comparative and international perspective / Pablo Fraser, Sakiko Ikoma -- Unpacking teacher differences in Didaktik and curriculum traditions : trends from TIMSS 2003, 2007, and 2011 / Armend Tahirsylaj, Kristina Brezicha, Sakiko Ikoma -- Exploring novice teachers' core competencies / Kent Seidel, Jennifer Whitcomb -- Indicators of quality in teacher education : looking at features of teacher education from an international perspective / Karen Hammerness, Kirsti Klette -- The influence of teacher education on mathematics teaching knowledge : local implementation of global ideals / Maria Teresa Tatto, Michael Rodriguez, Yang Lu -- Building and sustaining a quality STEM teacher workforce : access to instructional leadership and the interruptions of educator turnover / Edward J. Fuller, Lindsey Schrott -- No teacher is an island : how social networks shape teacher quality / Kira J. Baker-Doyle -- Conceptual understandings of democracy and values as aspects of teacher quality : the case of teacher education in Sweden / Bjo<U+0308>rn A<U+030a>strand -- Teachers' responses to changes in teacher evaluation policy in Korea and the United States / Peter Youngs, Jihyun Kim, James Pippin -- Current trends in the framing of teacher qualities / Stephanie L. Knight, Richard A. Duschl -- World culture and teacher quality: consensus, convergence, and conflict / Gerald K. LeTendre, Alexander W. Wiseman.
Includes index.
Print version record
Keywords: Education -- Teaching Methods & Materials -- General; Education -- General; Teaching skills & techniques; Educational strategies & policy; Education; Teacher effectiveness; Effective teaching; Comparative education